PENGARUH PENDAPATAN ASLI DAERAH (PAD), DAN DANA TRANSFER TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL: indonesia - ade onny siagian (Politeknik Ubaya, 2020)
This study aimed to test the effect of Own Source Revenue and Fiscal Balance Transfer on Capital Expenditure Budget Allocation on Provincial Government on D.I Yogyakarta on 2012 to 2018 based on Statistic Indonesian (BPS).This research uses descriptive quantitative approach, which is measure using multiple linear regression based method use SPSS 24.0. The population of this study is the district / city in the D.I Yogyakarta in 2012 to 2018. The sample is determined based on the census method which is taking a sample of the total population that is as many as 35 samples. The data used in this study are secondary data, that colleted on official website www.djpk.kemenkeu.go.id. The analytical methods used are descriptive analysis, analysis of classic assumption and multiple linear regression analysis with level of significance is 5%. Hypothesis testing is using regression partial test (t-Test) and the coefficient of determination test (R²).This result is Own Source Revenue and Fiscal Balance Transfer had a positive significant affect to Capital Expenditure Budget Allocation. This research is conducted 65,9% of factors influencing Capital Expenditure Budget Allocation. Future research may use others independent variable.